Oral health for achieving longevity. Issue 6 (19th April 2020) - Watanabe, Yutaka; Okada, Kazutaka; Kondo, Miyako; Matsushita, Takae; Nakazawa, Seitaro; Yamazaki, Yutaka
Abstract : Oral frailty is defined as a decrease in oral function accompanied by a decrease in mental and physical functions. Studies showing that people with oral frailty are at high risk of physical frailty, sarcopenia, severe conditions requiring nursing care and death have been reported in Japan. An increase in life expectancy and maintenance of teeth result in a decrease in the effect of the number of teeth. In contrast, a decrease in oral function as a result of aging has been suggested to have major effects on dysfunction and mortality risk. The present report is a narrative review of major clinical studies on the relationships of the number of teeth, dentures, occlusion and oral function with longevity, with the aim of providing information for future studies centered on oral function in Japan or overseas. This review clearly shows the relationships of the number of teeth, dentures, and occlusion with health and longevity. Recent studies have shown that, besides maintenance of the number of teeth, attempting to maintain or increase oral function, having a good diet and maintaining nutritional status are all linked to general health. Decreased oral function is a major risk factor for developing malnutrition and sarcopenia. Oral frailty, a new concept that has been recently introduced in Japan, is considered to have major effects on dental and oral health policies in Japan, in the old‐age group, and is expected to be reflected in the dental and oral health policies of various countries, as they also predict increased life expectancies. Geriatr Gerontol Int 2020; : – .